Ventos de Leste: uma aproximação às identidades musicais dos imigrantes de Leste - Guerra, Paula (2016)
This study aims to explore the identity representations in immigrants. The strong appreciation of culture tends to be reflected in subjective structures, as an inherent part of everyday life. We verified that the bindings and musical tastes resist migration, and even strengthened, since music and other art forms (poetry and dance) are an important means of resistance to loneliness, isolation, and other difficulties that immigrants are subject. Fifteen narratives were analyzed based on musical tastes and fruitions before the immigrant condition. The results suggest that music tends to occupy a prominent position in the daily lives of immigrants and cannot be reduced solely to a simple leisure activity. The traditional music of their countries of origin occupies a particularly important role and they are seen as a way to maintain essential daily contact with their cultures and traditions. The song plays a particularly important role as it allows trigger, actively, the collective memories that carry their countries of origin and express themselves in their mother tongue moods present. In summary, the strong element of collective memory present in traditional songs leads to it is given a great importance to its transmission to the second generation of immigrants, in particular through the occupation activities of leisure that immigrant associations promote the weekend.